SYNCHRONOUS AND ASYNCHRONOUS INTEGRATED PROJECT-BASED LEARNING IN ENGLISH LANGUAGE LEARNING - Suryani, Nyayu Yayu; Rahayu, Arum Putri; Rohani, Tri; Adiyono, Adiyono (Jurnal Smart, 2024)
The purpose of this study is to see how the integration of synchronous and asynchronous learning with PjBL in English language learning can increase students’ creativity and collaboration, as well as students' perceptions of PjBL that integrates synchronous and asynchronous English learning. This study employed both qualitative and quantitative research methods. The subjects of this study were students from the Islamic Education Study Program UIN Raden Fatah Palembang South Sumatera Indonesia. The findings showed that the integrated synchronous and asynchronous PjBL method was well-received by the students who were using it to learn English.